2015
DOI: 10.1007/s11605-015-2865-5
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Gastric Emptying After Pancreaticoduodenectomy: an Analysis of Risk Factors and Cost

Abstract: DGE is common after PD and contributes substantially to cost. DGE is frequently a secondary complication of abdominal infection, and interventions that limit such complications may be the most effective strategy toward preventing DGE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
68
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(73 citation statements)
references
References 45 publications
2
68
2
1
Order By: Relevance
“…Delayed gastric emptying most commonly occurs in the presence of other intra-abdominal complications, such as pancreatic leak or intra-abdominal abscess (secondary DGE). [17][18][19][20][21] Delayed gastric emptying can also occur in the absence of other intraabdominal complications (primary DGE). It has been hypothesized that pyloric denervation, lack of motilin from duodenectomy, loss of pyloric pump, gastric dysrhythmia, and inflammation may be underlying contributing mechanisms for DGE.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Delayed gastric emptying most commonly occurs in the presence of other intra-abdominal complications, such as pancreatic leak or intra-abdominal abscess (secondary DGE). [17][18][19][20][21] Delayed gastric emptying can also occur in the absence of other intraabdominal complications (primary DGE). It has been hypothesized that pyloric denervation, lack of motilin from duodenectomy, loss of pyloric pump, gastric dysrhythmia, and inflammation may be underlying contributing mechanisms for DGE.…”
mentioning
confidence: 99%
“…18,[22][23][24] Patient-related factors such as male sex, smoking history, and estimated blood loss have been shown to be associated with increased incidence of DGE. 19 Currently, there are no modifiable procedure-related factors that have been shown to be associated with decreased or increased incidence of DGE after PD. It has been reported that some configurations of the gastrojejunal (GJ) anastomosis may interfere with food passage.…”
mentioning
confidence: 99%
“…In a recent study by Okano et al (17), both variables were independently associated with infectious complications. Previous studies showed male gender to be related to specific complications, such as surgical site infection, pancreatic fistula and delayed gastric emptying (17)(18)(19). Recent studies have shown visceral fat as a predictor for pancreatic fistula and postoperative mortality (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Postoperative nausea/vomiting from delayed gastric emptying (DGE) is common; mean incidences range from 17% to 24%. 20,24,25 Pancreatic fistulas occur in 10% to 20% of cases; although the majority are clinically insignificant, inadequate management can lead to sepsis and hemorrhage, with 20% to 40% mortality. 20,[26][27][28] Sepsis rates may be around 9% to 16% 29,30 ; overall infection rates are difficult to ascertain, but are at least 17% to 20%.…”
Section: Complications After Surgery Alonementioning
confidence: 99%